Sleep and stress in athletes with disabilities around the 2021 Tokyo Paralympic games during the pandemic - Piotr Kazimierz Urbański; Britton W. Brewer; Michał Starczewski; Kwok Ng; Tomasz Tasiemski; Maciej Tomczak (Scientific Reports)
Abstract This research evaluated the relation and fluctuations in stress and sleep quality in athletes with disabilities (AwD) during the period before and after the 2020 Tokyo Paralympics, amidst the COVID-19 pandemic. Assessments were conducted every 3 months over a period of 10 months, encompassing three distinct pandemic phases. Results showed significant variations in perceived stress (F = 9.41, ηp2 = 0.09, p < 0.01) and sleep quality (F = 10.55, ηp 2 = 0.10, p < 0.001), with initial increased stress and poorer sleep, improving at the midpoint. Sleep quality components varied over time (p < 0.05), except for sleep medication use and daytime dysfunction. Results indicated a direct relationship where poor sleep potentially causes increased stress (β = 0.24, p < 0.01; β = 0.13, p < 0.05). The study underscores the need for regular stress assessments and development of sleep routines independent of external circumstances.